Comparing the effect of Centella asiatica L. and Acalypha indica L. treatment to carbonyl and glutathione level in the brains of old rats - Ninik Mudjihartini; Reni Paramita; Astrid Mariam Khairani Siregar; Estiana Filzadiyanti; Pungguri Ayu Nega Sarsanti; Erni Purwaningsih (Acta Biochimica Indonesiana, 2022)
Background: Free radicals in excessive concentrations damages cells and accelerate the aging process. Antioxidants found in Centella asiatica (CA) and Acalypha indica (AI) have the potential to prevent oxidative cellular damage. Objective: This study aimed to determine the effect of CA and AI on carbonyl and glutathione levels in the brain of older rats. Methods: 18-month age rats were treated using either AI, CA, or vitamin E. In addition, 18-month age and 2-month age untreated rats were used as a negative control. The brain carbonyl and glutathione levels were measured by Agustyanak and the Elmann method, respectively. Results: Treatment with CA significantly decreased brain carbonyl levels (2.87 nmol/mL) than the control rats (4.54 nmol/mL). Furthermore, treating AI did not reduce the brain carbonyl and GSH levels in aged brain rats. Conclusion: Centella asiatica can reduce the protein destruction that occurs with increasing age.